PENERAPAN MODEL PEMBELAJARAN PBL, TPS, DAN EXAMPLE NON EXAMPLE DENGAN MEDIA PASAR TERAPUNG DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PADA MUATAN IPAS DI KELAS III SD - Barus, Cesilia Faulina; Zain Ahmad Fauzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The problem in this research is the low critical thinking skills of student, caused by one-way, monotonous learning with minimal activity variation. The solution implemented is the use of a combination of PBL, TPS, and the Example Non Example model, supported by Floating Market media. The aim of this Classroom Action Research, conducted over three meetings, is to describe the improvement of students' critical thinking skills. The subjects were 12 third-grade students of SDN Benua Anyar 10 Banjarmasin. Data were collected through observation of students' critical thinking. The results showed a significant improvement: students’ skills increased from